Contextual fear memory retrieval by correlated ensembles of ventral CA1 neurons - Jessica C. Jimenez (Nature Portfolio, 2020)
The vCA1-BA projection is enriched in shock responsive neurons, which are necessary for fear memory encoding and become correlated with a network of neurons during retrieval. Here the authors show that the magnitude of vCA1 correlated activity is proportional to memory strength and requires the shock response during encoding.